Educational Policy Dilemma: New Student Admissions Policy Based on The Zoning System - Nuryanti Mustari (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study is to determine the implementation of a new student admission policy based on the zoning system. This study was conducted in East Luwu Regency, South Sulawesi, Indonesia because the implementation of a new student admission policy based on the zoning system caused several problems, such as ineffective socialization. This was carried out by the East Luwu Region Provincial Education Office Branch to the community which caused the parents or guardians and students not to understand the technical instructions for registration. Furthermore, this study used a descriptive qualitative method and data obtained are analyzed using the help of Nvivo12 Plus software. The result showed that policies are implemented based on the indicators of inter-organizational relationship behavior. This makes the East Luwu Region XII Provincial Education Office Branch and Senior High Schools to maintain mutual relationship with each other. Furthermore, it helps them to carries out organizational control and they are even professionals in completing their tasks. Meanwhile, based on these indicators, there have been many positive responses from the target group community but still, have a negative one. This is because of less optimal things from the implementation of new student admission policy based on the zoning system.